Teacher Training for 'Augmented Reading': The Living Book Approach and Initial Results - Maria Meletiou-Mavrotheris; Ana Rita Carrilho; Constadina Charalambous; Katerina Mavrou; Christiana Christou (MDPI AG, 2020)
Living Book-Augmenting Reading for Life, a three-year EU-funded Erasmus + project (September 2016-August 2019), exploited the affordances of augmented reality (AR) and other emerging technologies in order to address the underachievement of European youth in reading skills. The program developed an innovative approach that empowers teachers from upper primary and lower secondary schools (ages 9-15) to 'augment' students' reading experiences through combining offline activities promoting reading literacy with online experiences of books' 'virtual augmentation' and with social dynamics. Various professional learning activities were designed within the project, aimed at strengthening European teachers' profile and competences in effectively integrating the Living Book approach into their classroom activities, and in dealing with diversified groups of learners, particularly pupils from disadvantaged backgrounds. Teachers also received training in how to involve parents, and particularly those from disadvantaged and/or migrant backgrounds, in proreading activities to back the overall Living Book strategy at home. The current article provides an overview of the main phases of the Living Book project implementation, and of the program's key activities and outputs. It also outlines the content and structure of the 'Augmented Teacher' and 'Augmented Parent-Trainer' training courses developed within the project. Finally, it reports on the main insights gained from the pilot testing of the courses and the follow-up classroom experimentation that took place in the project partner countries.